CRIMINAL LEGAL PROTECTION FOR MEDICAL PERSONNEL IN THE RESOLUTION OF MEDICAL DISPUTES - Yosef Stefan Sutanto (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2024)
Medical disputes are a prevalent issue in medical practice, significantly affecting trust between medical personnel and patients. Moreover, the fear of legal repercussions often places medical professionals in ethical quandaries when making critical medical decisions. Therefore, ensuring adequate criminal law protections for medical personnel is essential to enable them to work with peace of mind and concentration. This research explores various forms of criminal law protection for medical personnel in managing medical disputes in Indonesia. Employing the judicial normative analysis method, it primarily examines Law No. 17 of 2023 on Health, supplemented by relevant literature and legal documents. Data collection involves analyzing legal texts and pertinent literature, using qualitative data analysis techniques. The study confirms that Law No. 17 of 2023 offers crucial legal safeguards for medical personnel, including the presumption of innocence, liability limitations, and equitable legal procedures. The Indonesian Medical Discipline Honor Council (MKDKI) plays a pivotal role in distinguishing between disciplinary and legal breaches, providing appropriate procedural frameworks. The establishment of the Indonesian Honor Council Mediation and Arbitration Institute (LMA-MKI) proves effective in resolving medical disputes through mediation and arbitration, promoting open communication, mutually beneficial solutions, and safeguarding confidentiality.